THE PROFOUND IMPACT OF SUNDAY SCHOOL CAREGIVERS IN SPIRITUAL GROWTH AND CHARACTER DEVELOPMENT - A. K. Sampeasang; Yonathan Mangolo (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
The study employs a descriptive approach to examine the significant role played by Sunday School Caregivers in shaping the character, faith, and spiritual development of children within the Toraja Church. The research aims to offer valuable insights into the diverse roles of Sunday School Caregivers and their contributions to facilitating spiritual growth and character development among the young generation. To collect data for this study, in-depth interviews were conducted with Sunday School Caregivers from various congregations within the Toraja Church region. The data gathered from these interviews provided valuable perspectives and experiences directly from the teachers, shedding light on their practices, challenges, and approaches in nurturing the faith of the children under their care. By exploring the lived experiences and insights of these dedicated educators, the study seeks to enhance our understanding of the profound impact of Sunday School teachers in shaping the spiritual journey of the future torchbearers of the Toraja Church.